PENGARUH AUDIT INTERNAL TERHADAP PERILAKU KECURANGAN DAN PENILAIAN KINERJA KARYAWAN PADA KOPERASI - Rini Febrianti (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2018)
This study aims to analyze the effect of internal audit on the behavior of fraud and employee performance assessment on the Employee Cooperative Republic ofIndonesia (KP-RI) Hanukarya Bandung. This study uses primary data obtained through questionnaires distributed to 31 respondents. The data collected by questionnaire are contained from 31 statements: 10 statements for Internal Audit as Free variable, 10 statements for Fraud Behavior and eight statements for Employee Performance Assessment as dependent variable . Objects in this study are employees of the Employee Cooperative Republic of Indonesia (KP-RI) Hanukarya Bandung. The method of analysis used is Pearson Correlation formula and to know how big influence of variable use method of determination. Statistical methods used to test the classical assumptions first, to test the hypothesis that is used t test and processed by using the program SPSS 23.0 ForWindows. The result of the research shows that the effect of Internal Audit on Fraud Behavior and Employee Performance Assessment is Good.